Forest Amenities and Location Choice in the Southwest - Michael S. Hand; Jennifer A. Thacher; Daniel W. McCollum; Robert P. Berrens (Journal of Agricultural and Resource Economics, 2008)
Locations with natural characteristics, such as forest, are thought to be attractive residential locations. This proposition is tested in the Southwest United States, composed of Arizona and New Mexico. This paper presents a conditional logit model of location choice estimated with household observations from the U.S. census, geographic information system (GIS) data, and county-level data. Results suggest that forest area, both in one's own location and nearby, increases the probability of choosing a location. But significant heterogeneity in location choices exists; an income effect and life-cycle effects on the demand for forest amenities appear to determine location choices.